Effect of dietary starch and exogenous α-amylase on in vitro gas production kinetics and lactation performance of lactating dairy cows - Grobbelaar, Theunis Johannes (Stellenbosch : Stellenbosch University, 2026)
Thesis (MScAgric)--Stellenbosch University, 2026.